2017
DOI: 10.1186/s40246-017-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating somatic tumor mutation detection without matched normal samples

Abstract: BackgroundObservations of recurrent somatic mutations in tumors have led to identification and definition of signaling and other pathways that are important for cancer progression and therapeutic targeting. As tumor cells contain both an individual’s inherited genetic variants and somatic mutations, challenges arise in distinguishing these events in massively parallel sequencing datasets. Typically, both a tumor sample and a “normal” sample from the same individual are sequenced and compared; variants observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Many tools and pipelines have been developed to call somatic mutations, and several studies compared software and pipelines to assess the performance [21][22][23][24] . However, the accuracy of somatic mutation calling can be largely affected by sequencing depth and mutation frequency, which bring these researches limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many tools and pipelines have been developed to call somatic mutations, and several studies compared software and pipelines to assess the performance [21][22][23][24] . However, the accuracy of somatic mutation calling can be largely affected by sequencing depth and mutation frequency, which bring these researches limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies, such "normal-tumor" paired strategy could be costly, thus it is interesting to find out if the "tumor-only" strategy could be a choice. Several studies have reported the performance of Mutect2 "tumor-only" mode and reported that tumor-only mutation detection resulted in a large number of false positive mutation sites 23,25 , thus may lead to inappropriate guidance for cancer therapies which is highly related to the patient safety and health care costs. Given these results, we did not perform the test between "tumor-only" mode and "normal-tumor" paired mode of Mutect2.…”
Section: Discussionmentioning
confidence: 99%
“…35 This work is in agreement with another recent study that identified the benefit of a PVD filter in conjunction with a pool of normal samples to tumor-only variant assessment. 36 This work also demonstrates the additional benefit of using clinically relevant variants, a list of sequencing artifacts, and the ClinVar database in tumoronly variant filtration.…”
Section: Order Of Operationsmentioning
confidence: 80%
“…However, it is important to note that calling somatic mutations is notoriously difficult, and that even though COSMIC somatic calls represent one of the best curated sets to date, somatic mutation call sets are often plagued by high falsepositive rates. [58][59][60] Therefore, it is best to interpret these mutational results conservatively, and to focus on what these patterns suggest about considering ancestry when studying the genomic variation of cancers. Ultimately, these mutational patterns represent ancestrally correlated genomic differences, and accounting for them can help preclinical and translational studies become more representative of one another.…”
Section: Discussionmentioning
confidence: 99%